2011
DOI: 10.5505/kjms.2011.08108
|View full text |Cite
|
Sign up to set email alerts
|

Our experiences with the in hospital cardiac arrests and their resuscitations

Abstract: AIM: We aimed to analyse the patients diagnosed with cardiac arrest in the emergency ward in accordance to their chronic illnesses, cardiac rhythm at the beginning of the cardiac arrest, the duration of the cardiopulmonary resuscitation and the mortality rates. METHODS: The records of 70 patients diagnosed with in-hospital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…O guztürk et al, in a 70-patient study, reported a mean age of 63.4 years a mean percentage of 58.6% [2] . In our study the mean age of the study population was 66.1 years and 63.9% of our patients were male.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O guztürk et al, in a 70-patient study, reported a mean age of 63.4 years a mean percentage of 58.6% [2] . In our study the mean age of the study population was 66.1 years and 63.9% of our patients were male.…”
Section: Discussionmentioning
confidence: 99%
“…Shockable rhythms constitute the majority of rhythms during cardiopulmonary arrest and such rhythms respond to CPR in a most favorably manner [2,3,6] . Studies before 2005 have shown that the survival rates were low in out-of-hospital ventricular fibrillation and it has been attempted to take necessary measures [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,15,16 In the guidelines accepted by The American Heart Association in 2000, teams should respond to a cardiac arrest and administer the first electrical shock in less than 2 min. 9,14,16 According to the CPR committee of The Broke Amy Medical Center, the CPR unit should reach the patient in arrest in less than 3 min and start treatment in less than 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The lower arrest rates in females might result from the fact that coronary problems, such as myocardial infarction and angina pectoris are less frequently observed among females. 15,16 In this study, the male/female rate and the mean age of the patients were compatible with the literature. 12,[17][18][19][20] Occurrence rates of CPA during the day and at night vary in several studies.…”
Section: Discussionmentioning
confidence: 99%